THE INFLUENCE OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Eti Ariyanti; Endang Susilo Wardani; Jaenudin (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to determine the influence of work discipline and work environment on employee performance both partially and simultaneously at PT Bogor Samudra Media Bogor West Java. This research method uses quantitative methods. The data collection method used was a questionnaire; the sample used in this research was 50 respondents. Multiple linear regression data analysis using the SPSS version 26 program and partial hypothesis testing results show that work discipline significantly affects employee performance. The work environment has a significant effect on employee performance, and simultaneously, work discipline and the work environment significantly affect employee performance. Determination shows that the work discipline and environment variables influence 86.2% of employee performance. In comparison, the remaining 13.8% is influenced by other factors not examined in this research.